2012
DOI: 10.5455/aim.2012.20.21-218-220
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Left Ventricular Diastolic Dysfunction in Sub-clinical Hypothyroidism

Abstract: Background:Adverse cardiovascular effect of hypothyroidism has been identified in many studies. Early identification of patients with sub-clinical hypothyroidism may lead to early treatment and thereby favourable effect on cardiovascular morbidity and mortality.Objectives:To find out the association of sub clinical hypothyroidism and left ventricular dysfunction and also to find out relationship between systolic and diastolic dysfunction in these patients.Material and Methods:A total 30 cases of sub clinical h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 9 publications
2
15
2
Order By: Relevance
“…The ejection fraction does not significantly vary between two groups. Our findings were correlated with various studies [6,7,13] .…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…The ejection fraction does not significantly vary between two groups. Our findings were correlated with various studies [6,7,13] .…”
Section: Discussionsupporting
confidence: 79%
“…Among 32 hypothyroid patients 6.25% were males and 93.75% were females while among 15 controls 13.33% were males and 86.66% were females, suggesting that female preponderance in our study. Most of the other studies [6][7][8] conducted had also female preponderance suggesting disease being more common in female population. Out of 32 hypothyroid patients 18 (56.2%) were subclinical while 14 (43.75%) patients presented with us as an overt hypothyroid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of subclinical thyroid dysfunction on the heart and the cardiovascular system is significantly less studied, and pathophysiological mechanisms of this relationship are still unclear (2). Studies showed that subclinical hypothyroidism (SHT) is associated with left ventricular remodeling, especially hypertrophy and diastolic dysfunction (3,4,5,6,7,8). However, the influence of SHT on the right ventricle (RV), as well as the effect of levothyroxine (L-T 4 ) therapy on RV remodeling, has been investigated in several studies which used only pulsed and tissue Doppler for the estimation of RV function (9,10,11,12,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…It is proved that the structural changes in the myocardium due to reduction of the thyroid gland function lead to a violation of intracardiac hemodynamics: reduced myocardial contractile function, its electrical instability, disruption of atrioventricular conduction, lengthening of diastole, reduced left ventricular ejection fraction [4,5]. Hypothyroidism is accompanied with the violation of functional state of the autonomic nervous system; it leads to the imbalance of sympathetic and parasympathetic influences on the heart and increases the variability of the QT interval, which significantly affects the course of both CHD and hypothyroidism [6].…”
Section: Introductionmentioning
confidence: 99%